PENINGKATAN KESEJAHTERAAN DESA MELALUI PROGRAM KEWIRAUSAHAAN DI ERA PANDEMI KELURAHAN TAMBAK BERAS, CERME KIDUL, NGABETAN, MOROWUDI, BANAJARSARI, JRAKAH KECAMATAN CERME, PURWOREJO JAWA TIMUR DAN JAWA TENGAH - Umaimah, Umaimah; Tiyastutik, Rifka Firdauzi (Jurnal Pengabdian Masyarakat dan Lingkungan, 2022)
Java Island is an island in Indonesia which is the 13th largest island in the world. With a population of approximately 160 million. Java's economy is highly dependent on the agricultural and plantation sectors, especially from farming in rice fields. Especially in the area of ​​East Java which is dominant in producing food products. The impact of the current outbreak of the Covid-19 pandemic is felt in many countries as well as in Indonesia, almost all provinces experienced significant changes due to this outbreak. One of the affected aspects is economic activity, therefore there is a need for understanding related to entrepreneurship. By running entrepreneurship, people will see opportunities and are always open to any positive input and changes so as to be able to bring the business to continue to grow rapidly. Socialization activities from KKN which were carried out online during the Covid-19 Pandemic which were carried out without meeting in person were provided by students of the University of Muhammadiyah Gresik together with the community in Cerme District and several villages in the District including Cerme Village, Banjarsari, Gedang Kulut, Morowudi in addition to that in the District Bungah and Purworejo District. This activity aims to improve and create a new product or new encouragement and motivation from welfare activities through entrepreneurship programs. The hope is that through their potential they are able to produce something useful for themselves and others. The community also actively participates in entrepreneurship socialization and online activities